Konstruksi makna pegiat Kelompok Dongeng Bengkimut - Nadia Dwi Putri; Edwin Rizal; Nuning Kurniasih (Universitas Padjadjaran, 2020)
Every activist’s introduce stories to children through storytelling. This study discusses the construction of meanings, motives, and experiences of ‘Kelompok Dongeng Bengkimut’ (Bengkimut Fairytale Group) activists. This research purpose was to discover the meaning, motives, and experiences of storytellers as activists. The research method was qualitative with a phenomenological approach, used were observation, interview, and literature study. Informants were seven active members in the ‘Kelompok Dongeng Bengkimut’, who had at least four years' experience in joining the group. Study results found that three meanings and two motives could be obtained from the ‘Kelompok Dongeng Bengkimut’ activists. The meaning possessed is a bearer of happiness, something pleasant, and a messenger. The 'Kelompok Dongeng Bengkimut' owned two motives, namely the motive of reason and purpose. The activist's first motive was a motive for a reason because (s)he was often told tales when (s)he was small, was also comfortable, and was not burdened. Whereas the motive for the purpose was to become an activist, bring up the culture of storytelling, challenge oneself, and introduce books to children. The activist's experience was storytelling in the Children's Ward at Hasan Sadikin Hospital, telling about his work, and storytelling to young and adult listeners. The constraints ever experienced were listeners who did not pay attention to fairy tales, storytelling in groups, and nervousness when storytelling. The conclusion the research that storytelling is meaningful for activist a bearer of happiness, something pleasant, and a messenger, the motive of reason and purpose.